Virtual learning environment in pedagogical management in private educational institutions in Huancayo, Peru - Cóndor Pielago, Mariluz Tomasa (2022)
Over the years, information and communication technologies have become specialized, to the same extent as virtual training. Thus, "Virtual learning environments have taken a step in pedagogical evolution by improving teaching-learning processes" Silva, J. (2011). However, we observe that the global crisis in which we are immersed by the Coronavirus (COVID-19) has required immediate changes in teaching practice. Accelerating the entry into virtuality that few teachers knew in the province of Huancayo Yangali, L. (2020). Therefore, this research study was developed to determine the relationship between the virtual learning environment and pedagogical management in private educational institutions in Huancayo, Peru. It responds to the research of quantitative approach, with a descriptive level, of basic type, with transversal non-experimental design correlal.  The sample consisted of 108 teachers of both sexes between 20 and 65 years of age from the province of Huancayo. This study was based on intentional non-probability sampling for accessibility. The technique was the survey and two questionnaires were administered: a questionnaire to measure the variable virtual learning environment composed of 36 items and another related to the pedagogical management of 19 items. The validity and reliability of the instruments was obtained through Cronbach's Alpha technique and expert judgment. The results when the Pearson statistical test was applied indicate that there is a high correlation (0.884) between the virtual learning environment and pedagogical management, curriculum planning (0.759), learning units (0.742), learning sessions (0.784) and didactic means and materials (0.825). In conclusion, we affirm that the virtual learning environment is positively related to pedagogical management in private educational institutions in Huancayo, Peru. We conclude this tool that provides synchronous and asynchronous communication in the management of materials, management of all participants and offering from the teaching field, technological support to teachers and students in terms of: teaching-learning process.  Bautista, G., Borges, F. & Fores, A. (2006).